Методологічні підходи до підвищення надійності оцінок бідності для регіонів України - Огай, M.Ю. (Інститут демографії та соціальних досліджень НАН України, 2006)
Изложены основные результаты исследований проблемы обеспечения статистической надежности показателей бедности для регионов Украины. Систематизировано методико-информационное обеспечение исследования бедности, установлено объективный характер существования проблемы недостаточной надежности показателей бедности для регионального уровня при их измерении по данным выборочного обследования. Разработаны научно-методические подходы композиционного оценивания. Сформулировано выводы и рекомендации по использованию предложенных методов при реализации мониторинга бедности в Украине. The basic results of the research of a problem of statistical reliability of poverty rates for the regional level of Ukraine are stated. On the basis of general statistical methods the problem of reliability of poverty measurement as a component of the State social policy is dealt with. Characteristics of the information base of research of poverty are submitted. Methodical approaches to application of the composite estimation are developed. Conclusions and proposals concerning concrete use of the offered methods are formulated at realization of Poverty monitoring in Ukraine.